Influence of penicllin allergy on antibiotic prescribing patterns and costs - Irawati, L.; Hughes, Jeffery; Keen, N.; Golledge, C.; Joyce, A. (The Society of Hospital Pharmacists of Australia, 2006)
Background: Antibiotic treatment for patients with community- acquired pneumonia (CAP) and previous history of penicillin allergy varies widely and can be more costly than for those with no history of penicillin allergy. Aim: To assess the influence of documented penicillin allergy on antibiotic prescribing for patients with CAP in an Australian hospital, and the clinical and financial consequences arising from changes to prescribing patterns. Method: The medical records of all patients 18 years and older admitted with CAP over a 15 week period were reviewed. The severity of patients' penicillin allergies was assessed through interview using a structured questionnaire and two groups formed: those with and without penicillin allergy. The antibiotic selections and treatment costs (drug plus accommodation costs) were then compared for the two groups. Results: 155 patients were reviewed (84 females, 71 males) with a mean age of 68 years (SD 18). Of these, 27 (17%) had documented penicillin allergies, of which 12 were classified as Severity 1 (anaphylaxis, urticaria), 12 as Severity 2 (rash, itch) and 3 as intolerance (gastrointestinal upset). Patients with a penicillin allergy were more likely to receive a cephalosporin, a macrolide and/or an aminoglycoside. This approach was in accordance with the recommendations of the Therapeutic Guidelines: Antibiotic (published in 2000), however the choice of cephalosporin in all cases was not. A history of penicillin allergy increased length of stay (p=0.054) and total cost of admission (p=0.051). Conclusion: Adherence of antibiotic prescribing to the Therapeutic Guidelines: Antibiotic for patients with penicillin allergies is variable. Patients labelled with penicillin allergy had greater drug costs and total admission costs. Thorough history taking to identify patients with true allergy versus intolerance may increase appropriate use of penicillins and reduce the use of more costly and potentially toxic alternative antibiotics.